Orenburg Nepluev Military School in Early 1840s: On Eve of Its Rebranding as a Cadet Corps - Yu. M. Gordeev (Научный диалог, 2025)
The relevance of this study is underscored by the 200th anniversary of military education in the Ural region. It is reported that on January 2, 1825, the Orenburg Nepluev Military School was established, laying the foundations for military education in this strategically significant area of Russia. This article analyzes the development of the institution during the early 1840s, from the approval of the “Regulations on the Orenburg Nepluev Military School” in 1840 to its rebranding as a cadet corps in 1844. At this stage, the paper characterizes the staffing situation within the institution and delineates the specific composition and training of its cadets in accordance with the 1840 regulations. The author notes that, despite Orenburg’s provincial status, which posed challenges in recruiting highly qualified personnel, the faculty of the institution should be recognized as one of its strengths. It is emphasized that the 1840 regulations considered regional specifics, facilitating further development and ultimately leading to its inclusion in the esteemed family of cadet corps across the Russian Empire. The study establishes that graduates from this institution played significant roles in various spheres of public life, not only in Orenburg but throughout the country.